Millet-based crop planting strategies in the Songhua River Region during the liaojin (907-1234 AD) dynasties: A case of the Luotong Mountain City site - Yang, Chun; Ban, Lin; Lv, Xiaohong; Li, Dong; Xu, Kun; Gao, Xiuhua; Wang, Chunxue (Frontiers in Plant Science, 2022)
Millet-based dryland agriculture is the traditional mode of agricultural cultivation in northern China and has been of great significance to the emergence and development of Chinese civilization. However, although they are both millet-based agricultural production methods, with various subtypes in different regions of northern China, and this difference is the best explanation for the fact that "one side of the land raises one side of people". In the Songhua River Region in northeast China, the ecological environment and abundant natural resources led to the slow development of agriculture, and it was only after the Liaojin Dynasties that a more mature farming industry was formed. Against this background, the agricultural utilization pattern of this region reflects a special characteristic that is different from the agriculture of the Chinese Central Plains. This paper examines the excavated plant remains from the Liaojin Dynasties in the Luotong Mountain City of the Songhua River Region and finds that the ancestors of this region were still engaged in a millet-based agricultural strategy during this period, with a certain lag compared to the Central Plains’agricultural strategy where Triticeae crops had become dominant. In addition, the crop structure with the millet-based agriculture of the region is also somewhat different from that of the Central Plains. Through comparative studies of surrounding sites and reference to historical documents, it was found that this difference in crop structure is a phenomenon unique to the Songhua River Region and is related to the dietary habits of the local settled Jurchen nomads, who ate barnyard millet meal.